2013
DOI: 10.1002/hep.26620
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic course of primary sclerosing cholangitis: Assessment by three-dimensional magnetic resonance cholangiography and predictive features of progression

Abstract: Magnetic resonance imaging (MRI) with magnetic resonance cholangiography (MRC) has become the radiologic standard of reference for diagnosis of primary sclerosing cholangitis (PSC). However, natural history of radiologic features of PSC is poorly known. In the current study, we aimed at analyzing the course of PSC using three-dimensional (3D) MRC and liver MRI to find predictive radiologic features of progression. PSC patients, followed up in our center, with at least two 3D MRCs performed in at least a 1-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
2
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 35 publications
4
126
2
3
Order By: Relevance
“…[15] The prognostic value of the Ishak and Ludwig staging system, as well as found that risk of progression was mainly dependent on the effects of biliary disease on liver parenchyma, rather than the effects of severe stricturing. [26] Necroinflammatory activity may predispose to development of CRS, however, no associations of histologic grading systems with CRS were shown. In PBC, associations between histology and CRS seem to be more pronounced.…”
Section: Discussionmentioning
confidence: 95%
“…[15] The prognostic value of the Ishak and Ludwig staging system, as well as found that risk of progression was mainly dependent on the effects of biliary disease on liver parenchyma, rather than the effects of severe stricturing. [26] Necroinflammatory activity may predispose to development of CRS, however, no associations of histologic grading systems with CRS were shown. In PBC, associations between histology and CRS seem to be more pronounced.…”
Section: Discussionmentioning
confidence: 95%
“…Multiple DS can be found in the same patient (12% in the study by Bjornsson et al) (34). Of note, the ERCP definition of DS is usually considered as not applicable to MRC, in particular in the extrahepatic ducts, given the insufficient spatial resolution of MRC (37,38) and the lack of hydrostatic pressure as provided by ERCP. Serum laboratory tests are neither sensitive nor specific enough to evaluate PSC progression (41), but in case of rapid increase of serum bilirubin levels and/or cholestatic liver enzymes (serum alkaline phosphatase, serum gamma glutamyl transferase) ERCP is indicated (6), especially in patients with a diagnosis of clinically significant hilar or extrahepatic strictures on MRC.…”
Section: Ercp In Established Pscmentioning
confidence: 99%
“…Of note, the visualization of the distal common bile duct and the peripheral intrahepatic ducts is still suboptimal using MRC (10,12). One study has suggested that a numerical score calculated based on three-dimensional MRC may predict progression of bile duct changes but the study lacked ERCP reference (17). A diagnostic MRC, because of its very high specificity for the diagnosis of PSC when diagnostic clinical and biochemical clues are present, obviates a confirmatory ERCP unless therapeutic procedures or ductal sampling are indicated (13,18 Whether or not to perform ERCP in patients with normal high-quality MRC depends on the level of clinical suspicion for PSC and impact of the diagnosis on patients management and prognosis.…”
Section: Esge/easl Recommend That As the Primary Diagnostic Modalitymentioning
confidence: 99%
“…On the other hand, unlike ERCP, MRC has the advantage of depicting biliary radicles beyond fully obliterative strictures; it yields pictures of hepatic morphology, and permits imaging of the hepatic parenchyma. Recently, novel protocols such as 3-dimensional MRC or adding delayed T1-weighted MRC to conventional T2-weighted scans have been reported and may also hold promise for monitoring disease progression [15][16][17] .…”
Section: Diagnosismentioning
confidence: 99%